Sustained heavy ethanol drinking affects CD4+ cell counts in HIV-infected patients on stavudine (d4T), lamivudine (3TC) and nevirapine (NVP) treatment regimen during 9 months follow-up period - Bbosa, Godfrey S.; Kyegombe, David B.; Anokbonggo, William W.; Mugisha, Apollo; Ogwal-Okeng, Jasper (Health, 2014)
Sustained heavy ethanol drinking is a common problem globally and ethanol is one of the most abused drugs among individuals of different socio- economic status including the HIV-infected patients on antiretroviral drugs. Ethanol is reward drug and a CNS depressant especially at high doses. The study determined the effect of sustained heavy ethanol drinking by HIV-infected patients on d4T/3TC/NVP regimen on CD4+ cell counts in Uganda using WHO AUDIT tool and chronic alcohol-use biomarkers. A case control study using repeated measures design with serial measurements model was used. The patients on stavudine (d4T) 30 mg, lamivudine (3TC) 150 mg and nevirapine (NVP) 200 mg and chronic alcohol use were recruited. A total of 41 patients (20 in alcohol group and 21 in control group) were screened for chronic alcohol use by WHO AUDIT tool and chronic alcohol use biomarkers. They were followed up for 9 months with blood sampling done at 3 months intervals. CD4+ cell count was determined using Facscalibur Flow Cytometer system. Results were then sorted by alcohol-use biomarkers (GGT, MCV and AST/ ALT ratio). Data were analysed using SAS 2003 version 9.1 statistical package with repeated measures fixed model and the means were compared using student t-test. The mean CD4+ cell counts in all the groups were lower than the reference ranges at baseline and gradually increased at 3, 6 and 9 months of follow-up. The mean CD4+ cell counts were higher in the control group as compared to the chronic alcohol use group in both WHO AUDIT tool group and chronic alcohol-use biomarkers group though there was no significant difference (p > 0.05). Chronic alcohol use slightly lowers CD4+ cell count in HIV-infected patients on d4T/3TC/NVP treatment regimen.
Keywords: Sustained Heavy Ethanol Drinking; CD4+ Cell Counts; HIV-Infected Patients; d4T/3TC/NVP Drug Regimen